Analisis Minat Beli Pedagang Terhadap Saus Tomat Mahkota - Leni, Leni; Winingsih, Rosa; Hidayat, Syamsul (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This research aims to analyze traders' buying interest in Mahkota Tomato Sauce by focusing on the factors that influence purchasing decisions. The method used was a quantitative survey with a questionnaire distributed to 100 traders in the Jakarta area. The results showed that 78.7% of traders were very likely to recommend Crown Tomato Sauce to other traders, while another 21.3% were very unlikely to do so. Additionally, 74.1% of merchants are very willing to pay more for Crown Tomato Sauce if the quality is improved, while another 25.9% are very unwilling. Factors that influence traders' buying interest include product quality, price, packaging and availability. Consumers tend to prefer products with good quality and appropriate prices. Apart from that, attractive packaging and consistent product availability are also important considerations in purchasing decisions. Based on these findings, it is recommended that Mahkota Tomato Sauce manufacturers focus on improving product quality, adjusting competitive prices, attractive packaging designs, and ensuring consistent product availability on the market to increase traders' buying interest.